Interest and Resilience in Online Mathematics Learning and Its Impact on Concept Understanding - Farman Farman; Fitriyani Hali; Muhammad Rawal (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2021)
This study aimed to determine students' interest in learning and mathematical resilience in online learning and their impact on understanding concepts. The research used in this study is Ex-post facto, namely research with a quantitative approach that aims to test or explain the relationship between variables through hypothesis testing. The research was conducted at SMA Negeri 8 Kendari class XI students in the 2020/2021 academic year. The research sample was 24 students of Class XI IPA 1 SMA Negeri 8 Kendari. Sampling using purposive sampling technique based on students' readiness to participate in online learning without network constraints. The instruments used in this study were questionnaires and tests. Questionnaires were used to obtain information about mathematical interest and resilience. In contrast, the test is used to obtain data about the ability to understand concepts. The data analysis technique used in this study was descriptive analysis technique and inferential analysis, which was carried out with the help of the SPSS 22 computer program. The results showed that students' interest in online learning had a significant influence on concept understanding. Likewise, students' mathematical resilience in online learning has a significant influence on conceptual understanding. The analysis results also show a significant effect of interest and resilience together on understanding mathematical concepts. The percentage contribution of the influence of interest and resilience variables on understanding mathematical concepts is 77.8%, while other variables influence the rest.